A study of lagundi oil the essential oil from Vitex negundo Linn. growing in the Philippines - Manalo, Josefina B. (1982)
Steam distillation of the leaves of vitex negundo linn. Fam. verbenaceae, gave a yield of 0.423% of essential oil. Thin-layer chromatography and gas liquid chromatography of the oil showed the presence at a least six components. Four predominant components out of the six identified as alpha-pinene, camphene,caryophyllene, and citral.